Combinatorial Number Theory
DOI: 10.1515/9783110925098.237
|View full text |Cite
|
Sign up to set email alerts
|

Extremal problems about asymptotic bases: a survey

Abstract: I give an account of results and open problems on asymptotic bases in general additive number theory, inspired and arisen from the paper "On bases with an exact order" by Paul Erdős and Ronald L. Graham, published in Acta Arith. 37 (1980), 201-207. I survey papers by Melvyn B. Nathanson, Xing-De Jia, John C. M. Nash, Alain Plagne, Julien Cassaigne, Bruno Deschamps and myself.-To Ron Graham, with my warmest wishes for his 70th birthday. 1. The Original Erdős-Graham Question I present here the original Erdős-Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…It is conjectured by Erdős and Graham [4] that there is a constant α such that X(h) ∼ αh 2 as h → ∞, but this remains open. The inequalities in (5) imply that X(1) = 1, X(2) = 4, X(3) = 7, but even the value of X(4) remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conjectured by Erdős and Graham [4] that there is a constant α such that X(h) ∼ αh 2 as h → ∞, but this remains open. The inequalities in (5) imply that X(1) = 1, X(2) = 4, X(3) = 7, but even the value of X(4) remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In [6,7], Grekos observed that in examples of bases A of order h that give large values of X(h), there are actually very few elements a ∈ A such that ord * (A \ {a}) = X(h). This led him to introduce the function…”
Section: Introductionmentioning
confidence: 99%
“…This seems far from being sufficient to conjecture that S(h) = h + 1 (a formula false for h = 1) rather than S(h) = 2h − 1 (for instance). Also, we may notice that the upper estimate in (1.5) gives a new proof of S(3) ≤ 6, an upper bound first proved in [8]. It is still undecided whether S(3) is 4, 5 or 6.…”
Section: Theorem 2 For Any Positive Integer H S(h) ≤ 2hmentioning
confidence: 96%
“…Motivated by this conjecture, Grekos himself proved that S(3) ≤ 6 < X(3) (see [8]) and announced, as a consequence of [6], that S(2) = 3 (actually, in [6], this result is proved under an additional minimality condition). But Grekos' proof was never published.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, in the general case, the best that is known is (h 2), h+1 S(h) X(h), the lower bound being due to Ha rtter [7]. Grekos' conjecture is that, for h>1, S(h)<X(h), a conjecture supported by S(2)=3<X(2) and S(3) 6<X(3) (proved in [3,5], respectively).…”
Section: Introductionmentioning
confidence: 99%